A photoacoustic Zn2+ sensor based on a merocyanine/xanthene-6-ol hybrid chromophore and its ratiometric imaging in mice. Issue 13 (14th June 2021) - Fang, Hongbao; Wang, Chengjun; Chen, Yuncong; Chen, Zhongyan; Yao, Shankun; Yang, Shiping; Dong, Lei; Guo, Zijian; He, Weijiang
Abstract : HD-Zn was constructed for reversible ratiometric PA Zn 2+ imaging in vivo . Zn 2+ titration experiments together with a theoretical study suggests that Zn 2+ chelation-induced ICT alteration in HD-Zn is responsible for its ratiometric PA sensing ability. Abstract : Accurate tracking of labile Zn 2+ fluctuation in vivo is essential for understanding the physiological and pathological functions of Zn 2+ . Photoacoustic (PA) Zn 2+ imaging is an attractive alternative for in vivo labile Zn 2+ tracking due to its larger tissue imaging depth than optical imaging, and exploring reliable design strategies to construct ratiometric sensors for Zn 2+ . PA imaging is especially demanded to overcome the interference from deviations of local sensor concentration and microenvironment. In this work, we designed a new ratiometric reversible PA sensor HD-Zn based on a merocyanine/2, 3-dihydro-1 H -xanthene-6-ol hybrid chromophore, with its phenol moiety being modified as a Zn 2+ chelator, 2-(bis(pyridin-2-ylmethyl)amino)phenol (BPAP). HD-Zn senses Zn 2+ in a ratiometric manner, showing an absorbance enhancement at 680 nm and a concomitant absorbance decrement at 750 nm. This endowed the sensor with ratiometric PA sensing ability for Zn 2+ . Zn 2+ titration experiments and theoretical study indicated that Zn 2+ chelation-induced ICT alteration of HD-Zn was responsible for the ratiometric PA sensing ability, and modifying the electron-donating hydroxyl group of this hybrid NIR chromophore to be a Zn 2+ chelator is a reliable strategy for constructing ratiometric PA sensors for Zn 2+ . Besides the ratiometric PA imaging ability for Zn 2+ in solution, HD-Zn also enables ratiometric PA imaging of labile Zn 2+ in living mice.